Cementing CO2 into C-S-H: A step toward concrete carbon neutrality. Issue 3 (28th March 2023) - Stefaniuk, Damian; Hajduczek, Marcin; Weaver, James C; Ulm, Franz J; Masic, Admir
Abstract: Addressing the existing gap between currently available mitigation strategies for greenhouse gas emissions associated with ordinary Portland cement production and the 2050 carbon neutrality goal represents a significant challenge. In order to bridge this gap, one potential option is the direct gaseous sequestration and storage of anthropogenic CO2 in concrete through forced carbonate mineralization in both the cementing minerals and their aggregates. To better clarify the potential strategic benefits of these processes, here, we apply an integrated correlative time- and space-resolved Raman microscopy and indentation approach to investigate the underlying mechanisms and chemomechanics of cement carbonation over time scales ranging from the first few hours to several days using bicarbonate-substituted alite as a model system. In these reactions, the carbonation of transient disordered calcium hydroxide particles at the hydration site leads to the formation of a series of calcium carbonate polymorphs including disordered calcium carbonate, ikaite, vaterite, and calcite, which serve as nucleation sites for the formation of a calcium carbonate/calcium-silicate-hydrate (C-S-H) composite, and the subsequent acceleration of the curing process. The results from these studies reveal that in contrast to late-stage cement carbonation processes, these early stage (precure) out-of-equilibrium carbonation reactions do not compromise the material's structural integrity, while allowing significant quantities of CO2 (up to 15 w%) to be incorporated into the cementing matrix. The out-of-equilibrium carbonation of hydrating clinker thus provides an avenue for reducing the environmental footprint of cementitious materials via the uptake and long-term storage of anthropogenic CO2 .